Interlocking Nail Fixation of an Opening Wedge Corrective Osteotomy for Femoral Malunion in a Dog - Hay, C. W.; Johnson, K. A. (Veterinary and Comparative Orthopaedics and Traumatology, 1995)
A young Malamute dog had a severe angular, shortening and rotational deformity of one femur due to malunion. An opening-wedge, corrective osteotomy was stabilized using an 8 mm diameter interlocking nail, with two screws proximally and two distally. Three months after the operation the osteotomy healed and lameness had resolved.An 8 mm diameter interlocking nail was used to stabilize a corrective osteotomy of a femoral malunion in a dog.
Keywords: Femur; malunion; corrective osteotomy; interlocking nail